U progu niepodległości ... Zamek prezydencki w Wiśle – zmienne znaczenia - Baniowska-Kopacz, Ewa (Instytut Archeologii i Etnologii PAN, 2014)
The article presents the Presidential Castle in Wisła as an anthropological place. When viewed as a type of a text, this architectural structure set within a particular space is filled with a range of meanings conferred on it by its architects/builders and its owners/users. It is also a narration about the history of the Castle itself and about the history of the people who lived in and near it. The history of the structure, although relatively short, is abundant in significant events which resulted in a change of ownership, the most important of them being the World Wars I and II and the birth of the 3rd Republic of Poland. These changes evoke a reflection as to what the Castle really is and what its true significances might be. Here, the focus is mainly on the period following World War I
25 cm
Keywords: Wisła; Presidential Castle; symbolism of historical objects; anthropological place